Motor development in non-microcephalic infants born to mothers with Zika Virus infection during pregnancy - Laís Rodrigues Gerzson; Carla Skilhan de Almeida; Juliana Herrero da Silva; Lavinia Schüler-Faccini (Universidade de São Paulo, 2020)
ABSTRACT This cross-sectional study sought to evaluate motor development in infants exposed to ZIKV born with normal head circumference (HC). Thirty one children, distributed into two groups, participated in the study: 15 whose mothers were infected by ZIKV during pregnancy, born with HC from −1.9 to +2 Z-scores, adjusted for sex and gestational age (exposed group); and 16 randomly selected infants without known prenatal exposure to ZIKV, paired by sex and age (control group). Alberta Infant Motor Scale (AIMS) was used to evaluate gross motor development. We found no significant difference between the exposed and control groups. However, considering that AIMS is a screening test that assesses only the gross motor development and the small size of our sample, infants exposed to ZIKV during pregnancy should be continuously evaluated for different aspects of their development.